Respons Pertumbuhan Aren (Arenga pinnata Merr.) Fase TBM Umur 4 Tahun terhadap Aplikasi Variasi Dosis Pupuk Tunggal dan Majemuk - Az Zahra, Fatimah; Ariyanti, Mira (Jurnal Agro Industri Perkebunan, 2025)
Sugar palm (Arenga pinnata Merr.) is an essential crop in Indonesia, valued for its sap used to produce sugar, alcohol, and biofuel. However, its long maturation period of 7-12 years requires optimal cultivation practices, including effective fertilization, to enhance productivity. This study aimed to evaluate the effects of inorganic fertilizers on the growth of sugar palm during the immature phase. The experiment was conducted at Ciparanje Experimental Field, Universitas Padjadjaran, using a randomized block design (RBD) with six treatments and four replications: the recommended dose of compound fertilizer, 75% and 50% of the recommended dose of compound fertilizer, the recommended dose of single fertilizer, and 75% and 50% of the recommended dose of single fertilizer. Observed variables included plant height, stem diameter, number of leaves, leaf area, canopy area, and chlorophyll content. Results showed that the application of single fertilizer at the recommended dose produced the best outcomes for all observed variables, particularly leaf number, leaf area, plant height, and chlorophyll content. High chlorophyll content was strongly correlated with optimal nitrogen fertilization, supporting enhanced photosynthesis. This study highlights the importance of selecting the appropriate type and dosage of fertilizer to improve sugar palm cultivation efficiency and provides valuable insights for optimizing practices during the immature phase.